Total Flavonoids Determination and Antioxidant Activity of Ethyl Acetate, Ethanol, and Methanol Extracts from Seluang Belum Root (Luvunga sarmentosa (Blume) Kurz.) - Nashrul Wathan; Muhammad Ikhwan Rizki; Amalia Khairunnisa; Hilneser Simamora (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Abstract: Flavonoids are phenolic compounds from nature that found in almost all parts of the plants. Seluang belum (Luvunga sarmentosa (Blume) Kurz.) root is one of the medicinal plants used by Dayak people in Central and South Kalimantan where in previous studies its part was contains flavonoids. This study aims to evaluate the best solvent for extracting flavonoid content and antioxidant activity using ethanol, methanol and ethyl acetate. The antioxidant activity performed by in vitro technique by DPPH assay. Total flavonoids content on the extracts of L. sarmentosa root determined using UV-Vis spectrophotometric with aluminium chloride method and calculated as quercetin equivalents (QE). The results showed the highest antioxidant activities confirmed for the methanol extract (IC50 = 80.33 ppm). The highest of total flavonoids contents was recorded for the ethanol extract (6.56 ± 0.006% w/w Quercetin Equivalent). The results showed that treatment effect of different solvent extraction was significant (sig <0.05) on total flavonoid and antioxidant activities from L. sarmentosa root.